EXPLORING THE VALIDITY AND PREDICTIVE POWER OF AN EXTENDED VOLUNTEER FUNCTIONS INVENTORY WITHIN THE CONTEXT OF EPISODIC SKILLED VOLUNTEERING BY RETIREES. Issue 1 (January 2014) - Brayley, Nadine; Obst, Patricia; White, Katherine M.; Lewis, Ioni M.; Warburton, Jeni; Spencer, Nancy M.
<x xml:space="preserve">Abstract</x> The current study examined the structure of the volunteer functions inventory within a sample of older individuals (N = 187). The career items were replaced with items examining the concept of continuity of work, a potentially more useful and relevant concept for this population. Factor analysis supported a four factor solution, with values, social and continuity emerging as single factors and enhancement and protective items loading together on a single factor. Understanding items did not load highly on any factor. The values and continuity functions were the only dimensions to emerge as predictors of intention to volunteer. This research has important implications for understanding the motivation of older adults to engage in contemporary volunteering settings.